Realizacja dziennikarskiej zasady prawdy i obiektywizmu podczas polskiej kampanii parlamentarnej 2015 r. - Leśniczak, Rafał (Political Preferences, 2017)
The realization of the journalistic principle of truth and objectivity during the Polish parliamentary election of 2015 The purpose of the paper was the evaluation of the way of respecting the journalistic principles of truth and objectivity by nationwide newspapers „Rzeczpospolita” and „Gazeta Wyborcza” in the context of the method of reporting the program assumptions of the two largest parties of the Polish political scene, Law and Justice (PiS) and Civic Platform (PO) during the Polish parliamentary campaign in 2015. The author used the method of content analysis of press, analysis method and synthesis method. Key words: media agenda setting, elections, newspapers, truth, objectivity